ASSESSING STUDENT SATISFACTION WITH ENGLISH COURSES AT UTMSPACE - Fariha Diyana Awang Ali; Farah Hamizah Muhd Zaimi; Nur Hazirah Mohd Bakhri; Nurnadirah Shahira Nazri; Nur Liyana Zakaria; Azhan Zulfadhli Handeri (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates student satisfaction with the English courses offered in the Diploma Programme at SPACE UTM, emphasizing course content, instructional delivery, workload, assessment, support services, and technological integration. Using stratified random sampling, a cross-sectional survey was conducted with 167 students, employing a structured Likert scale questionnaire to measure satisfaction levels. The results indicate that most students were satisfied with the relevance of the course content, the clarity of instruction, and the promotion of active participation. High satisfaction was also observed with workload balance and assessment transparency. Support services and technological integration received positive feedback as well. Nonetheless, areas for improvement were identified, such as broadening course content to address diverse interests, enhancing instructional methods to accommodate various learning styles, and offering additional guidance on managing workload. These findings provide valuable insights for improving English courses, contributing to curriculum development and instructional strategies in similar educational contexts.